2013
DOI: 10.1111/ijfs.12335
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physicochemical and functional properties of amaranth (Amaranthus hypochondriacus) protein isolates

Abstract: Summary Protein isolates from six amaranth lines/cultivars (APIs) were evaluated to study their physicochemical (hunter colour, protein content and zeta potential), structural (thermal and conformational) and functional (emulsification, foaming, water and fat absorption) properties. APIs had protein content, whiteness index and gel temperature in range of 79.4–85.4%, 41.17–54.26 and 87.8–91.8 °C, respectively. The Fourier‐transform infrared spectra of APIs revealed α‐helix, β‐sheets and random coil conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 39 publications
8
92
1
Order By: Relevance
“…However, Shevkani et al (2015) showed that proteins from kidney bean and field pea with higher thermal denaturation temperature could produce stronger heat-induced gels, which was different from the results in this research. Similar results were obtained in a recent study on amaranth protein isolates (Shevkani et al 2014). This difference could be caused by the difference between acid-induced and heat-induced gel mechanism.…”
Section: Rheological Propertiessupporting
confidence: 90%
“…However, Shevkani et al (2015) showed that proteins from kidney bean and field pea with higher thermal denaturation temperature could produce stronger heat-induced gels, which was different from the results in this research. Similar results were obtained in a recent study on amaranth protein isolates (Shevkani et al 2014). This difference could be caused by the difference between acid-induced and heat-induced gel mechanism.…”
Section: Rheological Propertiessupporting
confidence: 90%
“…Amide I and amide II are the characteristic bands found in the infrared spectra of proteins, arising from amide bonds. In amide I band, absorption leads to stretching vibration of C=O bond while as, in amide II band absorption leads primarily to bending vibration of N-H bond (Shevkani et al 2014). The secondary structure of protein is very sensitive to the location of both amide I and amide II band, because hydrogen bonding between the different elements of secondary structure involves the both C=O and N-H bonds.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…the ability of a protein to form and stabilize the emulsion by creating electrostatic repulsion on oil droplet surface. The emulsion stability index (ESI) refl ects the ability of the proteins to form and maintain a stable emulsion over a period of time by preventing fl occulation and coalescence of the oil globules (9). The soya and maize protein hydrolysate 05 had the lowest EAI of 3936.62 m 2 /g, while the pea fl our had the highest, 52 399 m 2 /g.…”
Section: Functional Analysis Of Vegetable and Cereal Proteinsmentioning
confidence: 99%
“…Several authors have compared the physicochemical and functional properties of buckwheat protein, soya protein isolate and casein (5,6,8). The functional characteristics of pseudocereals as quinoa and amaranth have also been reported in literature (5,9,10). Regarding cereals and other oilseeds, some authors have made comparisons among the protein functional properties of rice cultivars, peanut fl our and peanut protein concentrate as indicators of their potential use in food industry (11,12).…”
Section: Introductionmentioning
confidence: 99%